Cytoplasmic p27Kip1 promotes tumorigenesis via suppression of RhoB activity. Issue 1 (11th December 2018) - Calvayrac, Olivier; Nowosad, Ada; Cabantous, Stéphanie; Lin, Lin‐Po; Figarol, Sarah; Jeannot, Pauline; Serres, Murielle P; Callot, Caroline; Perchey, Renaud T; Creff, Justine; Taranchon‐Clermont, Estelle; Rouquette, Isabelle; et al.
Abstract: The cell cycle inhibitor p27 Kip1 is a tumor suppressor via the inhibition of CDK complexes in the nucleus. However, p27 also plays other functions in the cell and may acquire oncogenic roles when located in the cytoplasm. Activation of oncogenic pathways such as Ras or PI3K/AKT causes the relocalization of p27 in the cytoplasm, where it can promote tumorigenesis by unclear mechanisms. Here, we investigated how cytoplasmic p27 participates in the development of non‐small cell lung carcinomas. We provide molecular and genetic evidence that the oncogenic role of p27 is mediated, at least in part, by binding to and inhibiting the GTPase RhoB, which normally acts as a tumor suppressor in the lung. Genetically modified mice revealed that RhoB expression is preferentially lost in tumors in which p27 is absent and maintained in tumors expressing wild‐type p27 or p27 CK–, a mutant that cannot inhibit CDKs. Moreover, although the absence of RhoB promoted tumorigenesis in p27 −/− animals, it had no effect in p27 CK– knock‐in mice, suggesting that cytoplasmic p27 may act as an oncogene, at least in part, by inhibiting the activity of RhoB. Finally, in a cohort of lung cancer patients, we identified a subset of tumors harboring cytoplasmic p27 in which RhoB expression is maintained and these characteristics were strongly associated with decreased patient survival. Thus, monitoring p27 localization and RhoB levels in non‐small cell lung carcinoma patients appears to be a powerful prognostic marker for these tumors. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.